Pengembangan Ekonomi Desa melalui Kampung Garam (Studi Kasus Desa Bunder Kecamatan Pademawu Kabupaten Pamekasan Madura) - Wahyurini, Endang Tri; Hamidah, Emmy (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2020)
The purpose of this research was to obtain an overview and analyze the patterns of economic development in the village of Bunder, Pademawu Pamekasan District. The research employed descriptive analytical-qualitative methods. The research illustrated that the village of Bunder was a village on the coast with considerable salt potential. The majority of the people earned their living as salt farmers. Based on the Pamekasan Regent program to facilitate the management and economic development in the village, a thematic village was formed, the formation of these thematic villages based on the local potential of the region. Therefore, the village of Bunder was designated as "Village of Salt". The wealth and beautiful panorama of salt in this village motivated the community to build a "Salt Edu-tourism", a tourist destination besides conducting salt recrystallization efforts with a boiled salt system. The conclusion of the research was that the economic development of the village through the salt village was a form of competitive economic development.Tujuan dilakukan penelitian ini adalah untuk mendapatkan gambaran dan menganalisis pola pengembangan ekonomi desa di Desa Bunder Kecamatan Pademawu Pamekasan. Penelitian menggunakan metode deskriptif analitis kualitatif. Penelitian ini menggambarkan bahwa Desa Bunder merupakan   desa di pesisir dengan potensi garam yang cukup besar. Mayoritas masyarakatnya bermata pencaharian sebagai petani garam. Berdasarkan program Bupati Pamekasan untuk memudahkan dalam pengelolaan dan pengembangan ekonomi di desa perlu dibentuk desa tematik, pembentukan desa tematik ini berbasis potensi lokal wilayah tersebut. Oleh karena maka Desa Bunder ditetapkan sebagai “Kampung Garam”. Kekayaan dan panorama garam yang indah di desa ini memberikan motivasi kepada masyarakat untuk membangun sebuah destinasi “Eduwisata Garam” selain itu juga dilakukan usaha rekristalisasi garam dengan sistem garam rebus. Simpulan penelitian bahwa pengembangan ekonomi desa melalui kampung garam adalah sebagai bentuk pembangunan ekonomi yang berdaya saing.